PHILOSOPHY OF MANAGEMENT SCIENCE: ONTOLOGY, EPISTEMOLOGY, AND AXIOLOGY PERSPECTIVES - Harry Yulianto (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2021)
Philosophically, management was a collection of knowledge and beliefs that provide the basis for determining solutions to managerial problems. Every knowledge cannot be separated from philosophy because philosophy was the root of all human knowledge, both scientific and non-scientific knowledge. Management philosophy and science have a close correlation. The practice and science of management has a very deep philosophical dimension. Management cannot be separated from philosophy because without philosophy, management does not have a strong foundation. Without management, philosophy will be just knowledge that has not been put into practice. This paper aims to describe the philosophical conception of management science through philosophical exploration from the perspectives of ontology, epistemology and axiology. The ontological perspectives on management science was the essence of management practice. The epistemological perspective in management science was related to the scientific method approach as a standard procedure for studying management. And, the axiological perspective to the value that humans have to make various considerations about what is valued.